The Proportionality Test Models of Competing Rights Cases in the Civil and Common Law Systems: Lesson to Learn for Indonesia - Lailam, Tanto; Anggia, Putri; Chakim, M. Luthfi (Faculty of Law, Hasanuddin University, 2024)
This research focuses on the Proportionality test model of Competing Rights in practice in civil law countries (Germany and South Korea) and the Common Law System (United States and Canada). The research method used is a normative legal research method with statutory, comparative, and case approaches. The results show that the proportionality test is the